Corpos de Eva : olhares e paisagens sobre a nudez feminina no Brasil - Talita Iasmin Soares Aquino (2024)
The research investigates the construction of imaginaries about female nudity in Brazil,focusing on three television drama works: Dona Beija (1986), Xica da Silva (1996) and Hilda Furacão (1998). The methodology is inspired by the concept of pilgrimage (Ingold, 2012; 2015), which values the journey between textualities and allows the understanding of the construction of femininity and the exploration of women’s bodies in relation to the male and colonial gaze (Abril, 2010; Segato, 2021). Writing is conceived as a form of resistance and selfrecovery (Evaristo, 2020; Kiffer, 2021; hooks, 2019), seeking to challenge and transform norms that traverse the feminine. Highlighting scenes (Taylor, 2013) and landscapes (Ingold, 2021; Santos, 1988; 1995), the study develops a cartography (Rosário, 2008) of audioverbovisualities (Gutmann, 2021) through a performative gesture of articulation between the television works, their repercussions and the researcher’s experience. In an affective (Mendonça, 2023; Leal, 2023; Moriceau, 2020) and intersectional (Crenshaw, 2004; Gonzalez, 1980; 1984; 2020) approach, the research considers the complex interactions between race, gender and class, aiming to contribute to a critical understanding of Brazilian culture and the media influence on the social construction of femininity. The objective of the work is to promote reflection on the possibilities of resistance and transformation of hegemonic narratives.